1972
DOI: 10.1126/science.177.4052.887
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Skin Reactive Intestinal Cancer Antigen from the Carcinoembryonic Antigen of Gold

Abstract: Soluble fractions of human intestinal cancer and fetal intestinal cell membranes produced delayed hypersensitivity reactions in patients with intestinal cancer. These soluble fractions and perchloric acid extracts of intestinal cancer cells were fractionated by polacrylamide-gel electrophoresis. The Gold carcinoembryonic antigen was found in a region of the gels different from that of the skin reactive antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Studies by Thomson and Alexander (1973) on the MCI rat sarcoma indicated that the embryonic types of protein were reexpressed on the tumour-cell membrane simultaneously with tumour-specific transplantation antigens. Similar findings in human tumours were demonstrated by Hollinshead et al (1972), who showed that human colonic tumours expressed carcinoembryonic antigen at the same time as tumour-specific antigens. Kim et al (1975) suggested that the ability of cancer cells to survive and metastasize is directly attributable to antigen shedding.…”
supporting
confidence: 85%
“…Studies by Thomson and Alexander (1973) on the MCI rat sarcoma indicated that the embryonic types of protein were reexpressed on the tumour-cell membrane simultaneously with tumour-specific transplantation antigens. Similar findings in human tumours were demonstrated by Hollinshead et al (1972), who showed that human colonic tumours expressed carcinoembryonic antigen at the same time as tumour-specific antigens. Kim et al (1975) suggested that the ability of cancer cells to survive and metastasize is directly attributable to antigen shedding.…”
supporting
confidence: 85%
“…The characteristics in terms of specificity and chemical properties of the antigens isolated in these tumour extracts are still poorly resolved, though it is widely believed that, as with the experimental tumours, they are cell-membrane-associated proteins or glycoproteins. Nevertheless, it has been possible to determine that a colon carcinoma associated antigen demonstrable in soluble tumour extracts by delayed cutaneous hypersensitivity tests in cancer patients was separable by polyacrylamide gel electrophoresis from the carcinoembryonic antigen (Hollinshead et al, 1972), this being the most characterised abnormal tumour product in carcinoma of the colon (see following section).…”
Section: Human Tumour Associated Antigensmentioning
confidence: 99%
“…Moreover, specific immune complexes directed against CEA, when present, have been shown to inversely correlate with overall survival and disease stage (Kapsopulou-Dominos and Anderer, 1979;Staab et al, 1980;Mavligit et al, 1983;Ura et al, 1985;Konstadoulakis et al, 1994). Other groups (Collatz et al, 1971;LoGerfo et al, 1972;Sorokin et al, 1973) (Lejtenyi et al, 1971;Hollinshead et al, 1972;Mavligit et al, 1973a), although these reports are difficult to interpret as there are a mixture of potentially anergy-inducing factors inherent in these experiments. Differences in tumour antigen extraction technique, inactivation of CEA during the extraction process and the potential need for presensitized lymphocytes in stimulation assays may all affect the outcome of results (Mavligit et al, 1973b).…”
Section: Humoral and Cell-mediated Responses To Ceamentioning
confidence: 91%